2006
DOI: 10.1111/j.1365-2249.2006.03090.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice aberrantly expressing pyruvate dehydrogenase complex E2 component on biliary epithelial cells do not show primary biliary cirrhosis

Abstract: Summary Primary biliary cirrhosis (PBC) is an autoimmune disorder that specifically destroys biliary epithelial cells (BECs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The spontaneous animal model of PBC, such as C57BL/6 and MRL/lpr mice, was not stable, and the gene-modified model was not specific enough, and also with technological difficulties in some areas [13]. In 2005, Okada et al [14] established an animal model conforming to PBC in terms of serological and histological characteristics by injecting with polyI:C, an IFN-a inducer, to C57BL/6 mice, and then the model was verified to have an elevated level of Fasassociated death domain-like interleukin-1-b-converting enzyme inhibitory protein L (FLIP L , an anti-apoptotic protein) in hepatic CD4 ?…”
Section: Discussionmentioning
confidence: 98%
“…The spontaneous animal model of PBC, such as C57BL/6 and MRL/lpr mice, was not stable, and the gene-modified model was not specific enough, and also with technological difficulties in some areas [13]. In 2005, Okada et al [14] established an animal model conforming to PBC in terms of serological and histological characteristics by injecting with polyI:C, an IFN-a inducer, to C57BL/6 mice, and then the model was verified to have an elevated level of Fasassociated death domain-like interleukin-1-b-converting enzyme inhibitory protein L (FLIP L , an anti-apoptotic protein) in hepatic CD4 ?…”
Section: Discussionmentioning
confidence: 98%
“…So far, no causal link between the presence of the auto-ab and the development of PBC has been demonstrated. Notably, inducing aberrant PDC-E2 expression in a transgenic mouse did not cause the disease in animal models [38]. Moreover, reduction in the auto-ab titer of AMA did not improve the disease manifestation [18,38,39].…”
Section: Discussionmentioning
confidence: 93%
“…Pathogenetical models proposed so far consider as the crucial event the break down of T cell self tolerance to PDC epitopes. The generation of antibodies against PDC by themselves is not enough to damage the biliary ductules,as already mentioned [144] . The molecular mimicry model of self-tolerance breakdown was proposed as a more logical approach compared with the rather obscure concept of autoimmunity [161] .…”
Section: Current Views On the Pathogenesis Of Pbcmentioning
confidence: 94%
“…The results indicated that PDC-E2 expression BECs is not sufficient for the initiation of autoimmunity. Additional factors may be required to establish a model of PBC [144] .…”
Section: The Role Of Apoptosis In Pbcmentioning
confidence: 99%